A Synergy Model of Digital Leadership for Principals and Teachers to Overcome Technopedagogical Competency Disruption in Elementary Schools: A Theoretical Study - Ashfary Mukrim; Arismunandar (Journal of Innovative and Creativity, 2025)
ABSTRACT This study aims to develop a Digital Leadership Synergy Model that serves as a theoretical framework to address disruptions caused by the technopedagogical competency gap between principals and teachers in elementary schools. Through a theoretical study method involving analysis and synthesis of the latest literature, this study successfully identified the fundamental elements of digital leadership and technopedagogical competency. The results of the study map the profile of technopedagogical competency disruption, including the anatomy of the gap and its impact on the learning ecosystem. Based on these findings, a theoretical model was designed that visualizes the synergistic relationship between the main constructs of principal digital leadership and teacher technopedagogical competency, with collaborative mechanisms as the driving force. This model is also equipped with operationalization strategies, anticipation of challenges, and factors supporting its successful implementation in the context of elementary schools. As an outcome, this study formulates theoretical propositions that can be further tested. Thus, this study contributes a clear and applicable theoretical framework for stakeholders in building synergy to overcome digital competency disruption in elementary school environments.Keywords: Digital Leadership, Technopedagogical Competence, Synergy, Theoretical Model, Elementary School